PRELIMINARY STUDY ON PHOTONIC CRYSTAL-BASED EUPHOLUS CHEVROLATI BEETLE WING FOR REFRACTIVE INDEX SENSOR - Hidayah, Affi Nur (Teknologi Indonesia, 2016)
Micro and nanostructures from nature are very interesting for research and applicable technologies. One of theinteresting structures is beetle wing since they have unique optical properties. In this work, we have investigatedmorphology of nano and microstructure of beetle wing from Eupholus chevrolati species. We found that Eupholuschevrolati beetle wing species has perfect arrangement of nanostructure, known as photonic crystal structure. Thiskind of structure is very interesting due to its high reflectance at particular wavelength corresponding to its latticestructure. The result of SEM revealed three dimensional structure of photonic crystal structure exhibited insideEupholus chevrolati beetle wing species. Beetle wings have rigid and solid texture, so that is applicable for opticaldevices applications. Reflectance spectrum of beetle wings showed a distinctive reflectance peak, which indicatesphotonic crystal property. We observed clear reflectance peak position difference, about 20 nm wavelength, betweenbeetle wings in air and water. This difference corresponds to refractive index difference between air and water.Further development is still required to make beetle wings as refractive index sensor.